2012
DOI: 10.1021/nl3001088
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Induced Polarization in LaAlO3/SrTiO3 Heterostructures

Abstract: Demonstration of a tunable conductivity of the LaAlO(3)/SrTiO(3) interfaces drew significant attention to the development of oxide electronic structures where electronic confinement can be reduced to the nanometer range. While the mechanisms for the conductivity modulation are quite different and include metal-insulator phase transition and surface charge writing, generally it is implied that this effect is a result of electrical modification of the LaAlO(3) surface (either due to electrochemical dissociation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
162
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(182 citation statements)
references
References 39 publications
(50 reference statements)
19
162
1
Order By: Relevance
“…In contrast to the works on thick oxide films in literature, the electric field across the ultrathin LAO layers in our Pt/LAO/STO heterostructures is on the scale of MV/cm, which is high enough to trigger the drift of charged oxygen vacancies. Such electric-field-induced migration of oxygen vacancies between bistable configurations was also proposed by Bark and co-workers to explain the hysteretic response of switchable polarization in their piezoresponse-forcemicroscopy study of LAO/STO heterostructures [81]. Additionally, it is noteworthy that the good oxygendiffusion ability reported for Pt facilitates the electricfield-induced drift of oxygen vacancies in our Pt/LAO/ STO heterostructures [82].…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to the works on thick oxide films in literature, the electric field across the ultrathin LAO layers in our Pt/LAO/STO heterostructures is on the scale of MV/cm, which is high enough to trigger the drift of charged oxygen vacancies. Such electric-field-induced migration of oxygen vacancies between bistable configurations was also proposed by Bark and co-workers to explain the hysteretic response of switchable polarization in their piezoresponse-forcemicroscopy study of LAO/STO heterostructures [81]. Additionally, it is noteworthy that the good oxygendiffusion ability reported for Pt facilitates the electricfield-induced drift of oxygen vacancies in our Pt/LAO/ STO heterostructures [82].…”
Section: Discussionsupporting
confidence: 80%
“…Our calculated values for the 2DEG densities and for the critical thickness are in qualitative agreement with the majority of experimental reports; 4,[13][14][15][16][17][18][19]54 however, quantitative agreement is still lacking. One reason for the discrepancies might be the sensitivity of the results to the value of the dielectric constant.…”
Section: Alo2supporting
confidence: 88%
“…Cen et al 12 demonstrated the reversible process of inducing conductivity at the LAO/STO interface using a conductive tip at the surface of LAO by applying a field. Other groups [13][14][15][16][17][18][19] have observed similar phenomena and find a strong correlation between the environment to which the surface of LAO is exposed and the 2DEG density at the interface. Despite the important role played by the surface, there is a lack of experimental studies to determine the exact nature and structure of the LAO surface in this system.…”
Section: Introductionmentioning
confidence: 71%
“…Synchrotron X-rays [21] and combinations of scanning transmission electron microscopy and electron energy loss spectroscopy (EELS) [20,22] have been successfully used for obtaining localized electronic information on oxide hetero-interfaces. Scanning probe techniques are ideal for studying local electronic, magnetic, or electrochemical properties on surfaces [23][24][25][26]. Even more challenging is to access interfaces buried within multilayered structures.…”
Section: Chemical Structural and Morphologicalmentioning
confidence: 99%